2020
DOI: 10.1371/journal.pone.0230631
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of in-step and wrist weights on change of direction speed, accuracy and stroke velocity in junior tennis players

Abstract: The main aim of this study was to investigate the acute effects of the use of a weighting set (Powerinstep®) on measures of stroke velocity (StV), accuracy and change of direction speed (CODS) in junior tennis players. A within-subjects design was used to evaluate seventeen (6 female and 11 male) tennis players (mean ± SD; 16.5 ± 1.3 years old; 1.75 ± 8.4 m; 67.0 ± 8.1 kg; 22.04 ± 1.8 kg/m 2) on StV of three specific tennis actions (serve, forehand and backhand) and CODS for the following conditions: wearing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The discrete gradient method uses a generalized finite difference method to calculate the gradient of a function at discrete points. Compared with the classical finite difference method based on regular grid, the discrete gradient method can approximate the differential in a differential manner on an irregular grid or any discrete point cloud [ 16 ]. The specific derivation process of the discrete gradient method and the accuracy, stability, and convergence of the method have been described in detail in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…The discrete gradient method uses a generalized finite difference method to calculate the gradient of a function at discrete points. Compared with the classical finite difference method based on regular grid, the discrete gradient method can approximate the differential in a differential manner on an irregular grid or any discrete point cloud [ 16 ]. The specific derivation process of the discrete gradient method and the accuracy, stability, and convergence of the method have been described in detail in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the medicine ball group showing further improvements (11%) than the overloaded group (5%) in forehand velocity, this last design did not have a detrimental effect on precision as happened when performing MBT. Following this idea, Colomar et al (8) found that the use of light weights around the wrist did not negatively affect accuracy or SV, suggesting it may be a valid option for improvement in the long-term. Although literature is scarce regarding interventions with overweighted implements or limbs in tennis, investigations in other overhead sports may support the previously mentioned idea.…”
Section: Plyometrics Stretch Shortening Cycle Enhanced and Serve-spec...mentioning
confidence: 99%
“…7 Using wearable loads may enhance stride frequency, resulting into a better agility performance. 8 Extra weights inclusion during specific training exercise report improvements in biomechanical parameters and performance values. 9 Developing strength and resistance gains in specific running movements could cause better training-performance transference, 3,10 improvements also recorded in other sports as tennis, 8 based on performance changes including forces' direction (lateral and horizontal), unilateral propulsion, full range and speed performance, cyclic movements, and multi-planar field.…”
Section: Introductionmentioning
confidence: 99%
“…8 Extra weights inclusion during specific training exercise report improvements in biomechanical parameters and performance values. 9 Developing strength and resistance gains in specific running movements could cause better training-performance transference, 3,10 improvements also recorded in other sports as tennis, 8 based on performance changes including forces' direction (lateral and horizontal), unilateral propulsion, full range and speed performance, cyclic movements, and multi-planar field. 3 Several mechanical determinants that are overloaded by lower-limb wearable resistance may be influenced over time to produce positive speed adaptations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation